Trends in Maternal Mortality : 1990 to 2013 - WHO; UNICEF; UNFPA; World Bank; United Nations Population Division (Geneva: World Health Organization, 2014)
A number of initiatives that commenced in recent years are geared towards achievement of the fifth millennium development goal (MDG 5: improving maternal health), most notably the launch of the global strategy for women's and children's health in 2010 by the United Nations (UN) Secretary-General. Measuring the MDG 5 target of reducing the maternal mortality ratio (MMR) by three quarters between 1990 and 2015 remains a challenge. Accordingly, the maternal mortality estimation inter-agency group (MMEIG), comprising the World Health Organization (WHO), the United Nations Children's Fund (UNICEF), the United Nations Population Fund (UNFPA), the United Nations Population Division (UNPD), and the World Bank, together with a team at the National University of Singapore and University of California at Berkeley, United States of America, have been working together to generate internationally comparable MMR estimates. The estimates for 2013 presented in this report are the seventh in a series of analyses by the MMEIG to examine the global extent of maternal mortality. Consultations with countries were carried out following the development of the MMR estimates. The purposes of the consultations were: to give countries the opportunity to review the country estimates, data sources, and methods; to obtain additional primary data sources that may not have been previously reported or used in the analyses; and to build mutual understanding of the strengths and weaknesses of available data and ensure broad ownership of the results. This report presents global, regional, and country estimates of maternal mortality in 2013, as well as trends from 1990 to 2013. The report is organized as follows: chapter one gives introduction; chapter two provides an overview of the definitions and approaches for measuring maternal mortality. Chapter three is a detailed description of the methodology employed in generating the estimates. Chapter four presents the estimates and interpretation of the findings. Chapter five assesses the progress towards MDG 5. The annexes and appendices presents the sources of data for the country estimates, as well as MMR estimates for the different regional groupings for UNFPA, UNICEF, the UNPD, WHO, and the World Bank.